Chongqing sen lin = Chung king express [videorecording (DVD)] - Wong, Kar-wai, 1958-; Tarantino, Quentin; Lin, Qingxia; Leung, Tony Chiu Wai, 1962-; Wang, Fei, 1969-; Kaneshiro, Takeshi (Miramax Home Entertainment : Distributed by Buena Vista Home Entertainment, 2002)
Two intertwined romantic tales take place inside the Chʻung-chʻing high-rise shopping center in downtown Hong Kong. A policeman falls in love with a snack bar waitress while a house detective gets involved with a female drug dealer.